2015
DOI: 10.1021/acs.est.5b01693
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability-Based In Situ Remediation To Meet Future Lead (Pb) Standards in Urban Soils and Gardens

Abstract: Recently the Centers for Disease Control and Prevention lowered the blood Pb reference value to 5 μg/dL. The lower reference value combined with increased repurposing of postindustrial lands are heightening concerns and driving interest in reducing soil Pb exposures. As a result, regulatory decision makers may lower residential soil screening levels (SSLs), used in setting Pb cleanup levels, to levels that may be difficult to achieve, especially in urban areas. This paper discusses challenges in remediation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 126 publications
1
62
0
Order By: Relevance
“…Pb pollution has also been a serious threat to human health and food safety (Cuypers et al, 2016), especially harmful to young children (Datko-Williams et al, 2014). Over the last decade, evidence has been shown that Pb exposure-related health injury occur already at lower blood Pb levels than previously documented (Henry et al, 2015). Recently, the Centers for Disease Control and Prevention has lowered the reference value of blood Pb level to 5 μg dL -1 (Burns and Gerstenberger, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pb pollution has also been a serious threat to human health and food safety (Cuypers et al, 2016), especially harmful to young children (Datko-Williams et al, 2014). Over the last decade, evidence has been shown that Pb exposure-related health injury occur already at lower blood Pb levels than previously documented (Henry et al, 2015). Recently, the Centers for Disease Control and Prevention has lowered the reference value of blood Pb level to 5 μg dL -1 (Burns and Gerstenberger, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the effectiveness of Pb immobilization has been reported depending on the phosphate amendment, no significant differences were observed among H 3 PO 4 and/or Ca(H 2 PO 4 ) 2 amendments in the current study. The efficiency of the phosphorus amendment in Pb-contaminated soil has also been reported related to the type of soil and the nature and extent of the contamination [9].…”
Section: Leachability Of Pb In the Tclp Extractmentioning
confidence: 99%
“…Henry et al [9] demonstrated that the in situ remediation with phosphate amendments based on bioaccessibility assessments is the best approach. Phosphate (P) amendments are known to form stable Pb-P minerals (i.e., pyromorphite) [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, the EPA celebrated the completion of construction at the one thousandth Superfund site (EPA, 2015a). The cleanup of these hazardous waste sites has had numerous public health and economical benefits on the surrounding communities (Arndt et al, 1999; EPA, 2011; Gamper-rabindran et al, 2011; Henry et al, 2015). However, many Superfund sites remain as hazardous waste sites that pose significant threats to human health through contaminant exposure via soil, surface water, or ground water (Carlin et al, 2015; Jung et al, 2011; Messier et al, 2012; U.S.…”
Section: Introductionmentioning
confidence: 99%